Translational Medicine definition by the European Society for Translational Medicine. Issue 3 (March 2015) - Cohrs, Randall J.; Martin, Tyler; Ghahramani, Parviz; Bidaut, Luc; Higgins, Paul J.; Shahzad, Aamir
Abstract: Progress in the field of translational medicine (TM) within the last decade attests to the importance of the TM initiative in the context of more traditional academic health science centers. In many instances, these advancements have taken place without a clear definition of TM, which signifies the urgent need for a clear, consensus definition that would serve as an integrative blueprint for the various "versions" of TM definition. The various existing definitions are reflecting the diversity of institutional translational research and deployment programs. The European Society for Translational Medicine (EUSTM) is a global non-profit and neutral society whose principal objective is to enhance world-wide healthcare through the specific development and eventual clinical implementation and exploitation of TM-based approaches, resources and expertise. In this position article, the EUSTM defines TM as an interdisciplinary branch of the biomedical field supported by three main pillars : benchside, bedside and community. The goal of TM is to combine disciplines, resources, expertise, and techniques within these pillars to promote enhancements in prevention, diagnosis, and therapies . Accordingly, TM is a highly interdisciplinary field, the primary goal of which is to coalesce assets of various natures within the individual pillars in order to improve the global healthcare system significantly.